Controlling factors of seasonal and spatial variation of riverine CO2 partial pressure and its implication for riverine carbon flux - Liu, Jinke; Han, Guilin (The Science of the total environment, 2021)
Global carbon cycle is closely related to the earth's energy budget, because CO2 plays an active role in the global climate change. The higher CO2 partial pressure (pCO2) in inland water in comparison with atmosphere, causing a CO2 evasion from water to the air. However, the relationship between CO2 evasion, riverine carbon export, and hydrochemistry in watershed has remained largely unknown. This study collected 84 river water samples in Jiulongjiang River, to further address this subject on a small watershed scale. Water temperature fluctuation, riverine photosynthesis, and acidic matter input could not account for the seasonal variation of pCO2 in Jiulongjiang River. The spatial shifts of pCO2 were derived from the mixing process between headwater and soil influx. The soil influx with high pCO2 compensated the CO2 lost from evasion and caused pCO2 in Jiulongjiang River higher than the atmospheric level. The seasonal variation of pCO2 was caused by the precipitation difference between the wet season and dry season. The addition of rainwater significantly decreased the riverine pCO2 and HCO3− concentration in the wet season. The CO2 evasion rate in Jiulongjiang River was clearly higher than that in most worldwide large rivers. The annual CO2 evasion flux in Jiulongjiang River Basin was estimated about 2.48 × 105 T C/year, which was higher than the riverine total carbon export. The CO2 evasion rate exhibited significantly positive relationship with water surface area, indicating that the global CO2 evasion flux may be roughly estimated based on the observed regression relationship. Overall, our study indicated that it still requires collaborative effects to investigate the carbon dynamics in river water, more estimations of CO2 outgassing flux from river water under different hydrologic and geologic conditions are necessary. [Display omitted] •pCO2 in Jiulongjiang River exhibited seasonal difference.•The mixing between headwater and soil influx influenced riverine pCO2.•CO2 efflux from Jiulongjiang river is estimated at 2.48 × 105 T C/year•CO2 efflux is higher than the riverine carbon exported to the ocean.